TOXIN PRODUCTION BY ALTERNARIA-ALTERNATA IN TOMATOES AND APPLES STORED UNDER VARIOUS CONDITIONS AND QUANTITATION OF THE TOXINS BY HIGH-PERFORMANCE LIQUID-CHROMATOGRAPHY - OZCELIK, S; OZCELIK, N; BEUCHAT, LR (Elsevier, 1990)
Alternaria alternata strain 8442-3 was inoculated into tomatoes (Lycopersicon esculentum Mill.) and Red Delicious cultivar apples (Malus domestica Borkh.) Half of the lots of each fruit were shrink-wrapped in high-density polyethylene film. Wrapped and unwrapped fruits were incubated under darkness at 4,15 and 25-degrees-C for up to 5 weeks. A high-performance liquid chromatography method was developed to quantitate tenuazonic acid (TeA), alternariol (AOH), alternariol methyl ether (AME), and altenuene (ALT). Shrink-wrapping retarded, but did not completely inhibit growth in tomatoes for 3-7 days. Concentrations of up to 120.6 mg of AOH and 63.7 mg of AME per 100 g of tissue were produced in unwrapped tomatoes stored at 15-degrees-C for 4 weeks; 19.0 mg of ALT per 100 g of tomato tissue was produced after 3 weeks at 25-degrees-C. AOH, AME and ALT were also produced in unwrapped tomatoes stored at 4-degrees-C; however, no TeA was detected in decayed tomatoes, regardless of type of wrapping or storage temperature. Shrink-wrapping resulted in decreased production of AOH, AME, and ALT. Alternaria toxins were not detected in apples stored at 4 and 15-degrees-C. The higest concentration of AOH produced (48.8 mg per 100 g of tissue) was in unwrapped apples stored at 25-degrees-C for two weeks; 12.3 mg per 100 g of tissue of shrink-wrapped apples was detected after 5 weeks of storage at 25-degrees-C, while ALT reached 5.7 mg per 100 g after 4 weeks. TeA was not detected in apples infected with A. alternata.
Keywords: ALTERNARIA-ALTERNATA; MYCOTOXINS; TOMATO; APPLE